Journalistic treatment of climate change in the Peruvian newspapers El Comercio and La República (2013-2017) - Gonzales García, Carlos (Comunicación y Medios, 2018)
The research addresses the behavior of two Peruvian media (El Comercio and La Republica) on the existence and possible causes or consequences of climate change in the last three years (January 2014 to March 2017). For this purpose, taking as a basis the perspectives of the Agenda-Setting and the framing, we have proposed to identify thematic and framing from which this news is addressed by journalists, in order to show the way in which these printed please this phenomenon According to the results, there are no differences between one and another means in terms of frequency of coverage or space. However, throughout the study period, there is more media concentration on the expectations regarding the organization and implementation of the COP 20 Summit, held in December 2014, than on the possible impacts or consequences of the phenomenon.